UNFCCC side event: national adaptation planning in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Agriculture is hard hit by climate change. Are countries doing what it takes to plan adaptation in this important sector? Photos from UNFCCC COP19 Side Event, 15 November 2013, Warsaw, Poland.